Potensi Pengembagan Dye Sensitized Solar Cell (DSSC) dengan Sensitizer Zat Warna Alami dari Tumbuhan Asal Papua sebagai Alternatif Solusi Krisis Energi dan Pemanasan Global: The Potential for Development of Dye Sensitized Solar Cell (DSSC) with Natural Dyes Sensitizers from Papuan Plants as an Alternative Solution to the Energy Crisis and Global Warming - Agnes Dyah Novitasari Lestari (JISTECH: Journal of Information Science and Technology, 2014)
Currently, the energy crisis and global warming are an important issue internationally, including Papua. Various attempts were made to overcome these problems, for instance the development of alternative energy that does not cause global warming: the solar energy harvested by the solar cells (solar cells). There is an obstacle for solar cell applications: the high production costs. This problem is solved by the discovery of a type of solar cell Dye Sensitizized Solar Cell (DSSC).Utilization of local potential will reduce the cost of fabricating such a device. Papua is well know for its flora abundance and diversity, one of which is a natural dye-producing plants. Color produced by these plants show content that has a group of compounds that can absorb light (chromophore) contained therein. The content of this chromophore compounds provide potential it can be used as a sensitizer in DSSC, thus resulting DSSC that is relatively cheap for Papua.